Foreign ownership restrictions and share prices in the China capital market. - Lee, Boon Leng. (2009)
This paper looks briefly at the development of the Shanghai and Shenzhen stock markets in the context of China's goal to attract foreign capital to modernise and integrate its economy to the global economy. The analysis of the stock returns revealed that the returns on B shares in Shenzhen generally exhibit little or no correlation with international factors while those in Shanghai do exhibit some correlation. In addition, liquidity as measured by the ratio of the volume of B shares to total volume of A and B shares only explain the returns of Shenzhen B shares. The only factor that explains the returns on both Shanghai and Shenzhen B shares is the effects of firm size. Generally, the results suggest that the Shenzhen B shares have some diversification value while Shanghai B shares are not totally segmented from international factors.